2020
DOI: 10.1097/icu.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes in retinal detachment: the potential role of rho-kinase inhibitors

Abstract: Purpose of review Retinal detachment initiates a series of events that lead to degenerative changes in retinal synaptic architecture as well as the well-known phenomena of gliosis and photoreceptor apoptosis. Retinal reattachment does not always result in complete visual recovery, even if the fovea is not directly involved in the detachment. Rho-kinase (ROCK) inhibitors may mitigate some of these deleterious changes including disruption of synaptic architecture, photoreceptor apoptosis, and initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The synaptic damage, although the mechanism is not known, is linked to activation of the RhoA pathway by the RD (Wang et al, 2016). Therefore, it has been suggested that inhibition of the RhoA pathway can improve visual outcomes after reattachment surgery (Halász et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synaptic damage, although the mechanism is not known, is linked to activation of the RhoA pathway by the RD (Wang et al, 2016). Therefore, it has been suggested that inhibition of the RhoA pathway can improve visual outcomes after reattachment surgery (Halász et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by previous animal studies which have reported damage to the synapse between photoreceptor and bipolar cells in both attached and detached retina (Halász et al, 2021; Townes‐Anderson et al, 2017; Wang et al, 2016). This synaptic damage is due to rods retracting their presynaptic terminals and cones losing their synaptic invaginations (Halász et al, 2020). Reattachment of the retina does not restore all the synapses so it has been proposed that the synaptic changes can be the cause of incomplete visual recovery after anatomical successful reattachment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although CamkIIα is up-regulated in IRD 21 , this protein is expressed in only up to 10% of normal primate RGCs 38 . Excised human surgical retinal specimens taken from patients undergoing retinal detachment surgery offer a suitable in vitro model of outer retinal degeneration because of characteristic changes in the photoreceptors and postsynaptic cleft 39 , 40 . Human surgical retinal explants demonstrated expression of bReaChES two weeks following exposure to the treatment vector in tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subfoveal viral gene therapy has been associated with various adverse effects, such as RPE alterations, retinal thinning, foveal morphological changes, vision loss, and the variable duration of clinical effects [281,294,[296][297][298]. ROCK inhibitors may improve synaptic remodelling and ameliorate these negative effects in the future [299]. Finally, the limited lateral diffusion of subretinal agents may not fully suppress complement activation in distal retinal sites [282].…”
Section: Subretinal Therapiesmentioning
confidence: 99%